Periodontal condition in rats with experimental diabetes mellitus after orthodontic surgery - Azari Mehrdad Mohammad Ali (Kazimierz Wielki University, 2019)
Background. Determine periodontal condition in rats with experimental diabetes mellitus after orthodontic surgery. Methods. In rats, type 1 diabetes mellitus (DM1) was reproduced with aloxane (100 mg / kg, intraperitoneally) once. Orthodontic surgery was performed by fixing the spring, starting from the 12th day. Animal euthanasia was performed on the 35th day of the experiment. The activity of urease, lysozyme, catalase, elastase, as well as the content of malondialdehyde (MDA) and hyaluronic acid were determined in the gum homogenate. In the alveolar bone homogenate, the activity of alkaline phosphatase (AlP) and acid phosphatase (AcP) and elastase was determined, as well as the content of calcium and protein. The antioxidant-prooxidant index (API) was calculated by the ratio of catalase activity and MDA content, and the degree of dysbiosis according to A. P. Levitsky was calculated by the ratio of the relative activities of urease and lysozyme. The mineralizing activity (MA) was calculated by the ratio of the activity of alkaline phosphatase (AlP) and AcP in the bone tissue and the mineralization (MD) degree was calculated by the ratio of the concentration of calcium, and protein. Results. In rats with DM1, the level of elastase, urease, MDA and the degree of dysbiosis increase in the gum, however, the level of lysozyme, hyaluronic acid, and the API index decrease. In the bone tissue of the periodontium of rats with type 1 diabetes, the level of alkaline phosphatase and MA decreases, but the level of AC increases. Orthodontic surgery significantly reduces the degree of dysbiosis in the gums and shows a tendency to increase API and decrease elastase activity. After orthodontic surgery, rats significantly increase the level of alkaline phosphatase and MA. Conclusion. With type 1 diabetes, periodontitis, dysbiosis develops and the mineralizing activity of periodontal bone tissue decreases. Orthodontic surgery tends to improve periodontal conditions.